SKRINING FITOKIMIA DAN UJI TOKSISITAS MENGGUNAKAN BRINE SHRIMP LETHALITY TEST (BSLT) DARI EKSTRAK DIKLOROMETANA RIMPANG TEMU KUNCI (Boesenbergia rotunda) - Jonathan, Jonathan; Ruga, Ritbey; Hairani, Rita (JURNAL ATOMIK, 2024)
The rhizome of Boesenbergia rotunda (temu kunci) is one of medicinal plants having potential for medicinal, supplementary food and drink due to its biological activities. The aims of this research are to identified the secondary metabolite compounds present in the dichlorometane extract of finger-root rhizomes through phytochemical screening using thin layer chromatography (TLC) method and to investigated its toxicity against Artemia salina L. shrimp larvae by using Brine Shrime Lethality Test (BSLT). The result of phytochemical analysis showed that the dichloromethane extract contains secondary metabolite compounds including flavonoids, phenolics and triterpenoids while the toxicity test of the extract showed its LC50 value of 303.68 µg/mL. It was indicated that the extract could be classified as toxic.